2017
DOI: 10.1088/1361-6463/aa96f2
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium and vanadium nitride thin films grown by high power impulse magnetron sputtering

Abstract: Thin vanadium and vanadium nitride films were grown on SiO2 by non-reactive and reactive high power impulse magnetron sputtering (HiPIMS), respectively. The film properties were compared to films grown by conventional dc magnetron sputtering (dcMS) at similar conditions. We explored the influence of the stationary magnetic confinement field strength on the film properties and the process parameters. The deposition rate is much lower for non-reactive sputtering by HiPIMS than for dcMS. Furthermore, for both dcM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…Upon thermal treatment, a small shift towards a greater diffraction angle was noticed, which may be attributed to stress relaxation, with consequent reduction in the lattice constant. The fcc δ-VN phase formation under the prevailing conditions of power density (12.7 W•cm −2 ) and nitrogen gas flow (14 sccm) as well as the resulting film growth rate (3.83 nm•min −1 ) confirm the findings reported earlier [16,17].…”
Section: Morphology and Compositionsupporting
confidence: 88%
“…Upon thermal treatment, a small shift towards a greater diffraction angle was noticed, which may be attributed to stress relaxation, with consequent reduction in the lattice constant. The fcc δ-VN phase formation under the prevailing conditions of power density (12.7 W•cm −2 ) and nitrogen gas flow (14 sccm) as well as the resulting film growth rate (3.83 nm•min −1 ) confirm the findings reported earlier [16,17].…”
Section: Morphology and Compositionsupporting
confidence: 88%
“…Bradley et al [19] reported on a deposition rate increase by a factor of 2 for a Ti target when the magnetic field strength at the target was reduced by 45%. In addition, while weakening |B| by 82% a factor of 2.6 higher deposition rate was observed while depositing vanadium films by HiPIMS, although for the weaker magnetic field the films exhibited significantly higher surface roughness and were not as dense [28].…”
Section: Introductionmentioning
confidence: 89%
“…The current initiation delay time changes linearly in the 0.33 -0.73 Pa range and increases dramatically at lower pressures. Previously we have reported the increased delay time with decreasing Ar pressure when sputtering a tantalum target [38] and for a vanadium target in Ar/N 2 mixture [31]. Due to its stochastic nature, the delay time can be explained statistically as described by Yushkov and Anders [39].…”
Section: A Discharge Current and Voltage Waveformsmentioning
confidence: 98%
“…This high electron density leads to a high ionization fraction of the sputtered material. As a result HiPIMS presents denser [27][28][29], void free [30] and smoother coatings [28,30,31] can be grown by HiPIMS and they are claimed to have the same composition as the target over wide range of pressures [32]. This is important since dcMS has been found to present 2.3 at.% change in iron content of Py by changing the pressure in the 0.38 -2.4 Pa range [18] which can have significant effect on the magnetic properties, as discussed e.g.…”
Section: Introductionmentioning
confidence: 99%